A Genome‐Wide Association Study of Non‐Photochemical Quenching in response to local seasonal climates in Arabidopsis thaliana - Tepsuda Rungrat; Andrew A. Almonte; Riyan Cheng; Peter J. Gollan; Tim Stuart; Eva‐Mari Aro; Justin O. Borevitz; Barry Pogson; Pip B. Wilson (Wiley, 2022)
Field‐grown plants have variable exposure to sunlight as a result of shifting cloud‐cover, seasonal changes, canopy shading, and other environmental factors. As a result, they need to have developed a method for dissipating excess energy obtained from periodic excessive sunlight exposure. Non‐photochemical quenching (NPQ) dissipates excess energy as heat, however, the physical and molecular genetic mechanics of NPQ variation are not understood. In this study, we investigated the genetic loci involved in NPQ by first growing different Arabidopsis thaliana accessions in local and seasonal climate conditions, then measured their NPQ kinetics through development by chlorophyll fluorescence. We used genome‐wide association studies (GWAS) to identify 15 significant quantitative trait loci (QTL) for a range of photosynthetic traits, including a QTL co‐located with known NPQ gene PSBS (AT1G44575). We found there were large alternative regulatory segments between the PSBS promoter regions of the functional haplotypes and a significant difference in PsbS protein concentration. These findings parallel studies in rice showing recurrent regulatory evolution of this gene. The variation in the PSBS promoter and the changes underlying other QTLs could give insight to allow manipulations of NPQ in crops to improve their photosynthetic efficiency and yield.